Clinical Neuropsychology in Germany - Kasten, Erich (Frontiers in Psychology, 2022)
Clinical neuropsychologists have been working in Germany since the 1980s, and specific training in the discipline has been available since 1993. The qualification currently requires three years of practical training, 400 hours of theoretical learning, 100 hours of supervision, 5 reports on patients and an oral examination. After its completion, neuropsychologists can work as employees in clinical settings. For a substantial period of time, neuropsychologists working in their own practices faced complex challenges in working with outpatients, whose health insurers did not cover the cost of this treatment. State approval of neuropsychological diagnostic procedures and therapy was achieved in 2011, on the basis of evidence showing the method’s high effectiveness; statutory health insurers therefore now pay out for delivery of these services on an outpatient basis, too. In Germany, neuropsychologists work in all areas of the diagnosis of functional disorders, with children, adolescents, adults and older adults, and carry out treatment. Clinical neuropsychologists provide patients with individualised tools for managing their brain damage, supply exercises and tasks for them to undertake at home, and give input on administrative matters, such as determining the degree of a patient’s disability. Treatment takes place in close collaboration with members of related professions, such as physiotherapists, occupational therapists and speech therapists. Neuropsychologists also work as assessors, investigating, for example, the extent of a patient’s ability to work after sustaining CNS damage or the need for medical retirement. The earnings of clinical neuropsychologists vary widely, currently averaging between 3,000 and 4,000 € gross per month for employed neuropsychologists; self-employed neuropsychologists in their own practices can currently bill statutory health insurers for around 100.00 € per hour. Despite the generally good working conditions in this discipline, Germany is suffering from a shortage of clinical neuropsychologists. An approximate total of 800 psychologists have completed training in this field, while around 50,000 patients could benefit from neuropsychological treatment every year.